Modeling the roles of carbon nanotubes and interphase dimensions in the conductivity of nanocomposites - Zare, Yasser; Yop Rhee, Kyong; Park, Soo-Jin (Results in physics, 2019)
The influences of interphase regions on the percolation threshold and electrical conductivity of nanocomposites polymer/carbon nanotubes (CNT) nanocomposites (PCNT) have been ignored in previous articles, although the interphase layer around CNT can encourage the conductivity. In this paper, the dimensions of CNT and surrounding interphase suggest the percolation threshold of CNT in PCNT. The comparisons between predictions and experimental measurements in several samples confirm the suggested equation. Moreover, the effective volume fraction of CNT and the fraction of networked CNT in the presence of interphase zones are expressed. Finally, a model is developed to investigate the roles of CNT and interphase dimensions as well as percolation threshold and CNT conductivity in the conductivity of PCNT. Thin CNT and thick interphase increase the effective volume fraction of nanoparticles in PCNT, whereas the CNT length is ineffective. A thick interphase and a high concentration of thin and long CNT grow the percentage of networked CNT and the conductivity of PCNT. The conductivity directly correlates to the CNT conductivity, while the smallest percolation threshold causes the highest conductivity. Additionally, a high waviness worsens the percolation threshold, the network size and the CNT conductivity resulting in a poor conductivity in nanocomposites.